Dielectric surrounding bleaches the optical bond between a microdisk resonator and a straight optical waveguide. (December 2020) - Raskhodchikov, A V; Scherbak, S A; Kryzhanovskaya, N V; Lipovskii, A A; Zhukov, A E
Abstract: We performed a numerical study of a surrounding medium influence on coupling efficiency between a microdisk resonator supporting optical whispering gallery modes and a straight optical waveguide. Quality factors of the modes and relative optical power coupled to the waveguide were calculated using COMSOL Multiphysics environment. It was shown that the most efficient coupling takes place when propagation constants of the modes of the microdisk and the waveguide match. The coupling can be significantly strengthened by increasing the index of the surrounding medium.